The Effects of Economic Sanctions on the Informal Economy - Ioana M. PETRESCU (Management Dynamics in the Knowledge Economy, 2016)
Countries often use economic sanctions to coerce other countries to change certain policies of which they do not approve. However, if sanctioned countries smuggle goods over the border, use informal financial intermediaries, and develop black markets to trade sanctioned goods, sanctions end up having a smaller impact, sanctioned countries have little incentive to modify their policies, and sanctions are more likely to fail. This paper is the first study to test empirically whether sanctions affect informality. I compile data from different studies about the size of the informal market for 147 countries over 46 years. I use these data to analyze the relationship between the size of the informal market adjusted by the size of the population and economic sanctions. I also estimate at the impact of economic sanctions on other activities associated with informal activities. I find that informal markets increase when a country is being sanctioned and the effects are larger when the economic sanction has strong international support. I also find that the type of sanction, trade or financial, is not an important determinant of the informal market size and that sanctions also lead to increases in robbery rates and corruption.